Creating hope: Assisting Veterans with Job Search Strategies using Cognitive Information Processing Theory. Issue 2 (June 2017) - Buzzetta, Mary; Hayden, Seth C. W.; Ledwith, Katherine
Abstract : Providing effective employment services to today's veterans is essential. Given the high unemployment rate that currently exists for the veteran population, it is essential that career development professionals consider ways to effectively address their needs. This article highlights the complexities veterans experience in the job preparation and job search processes, as well as current efforts addressing the veteran unemployment concern. A clinical case study shows how cognitive information processing theory, a theory of career problem solving and decision making, can be used as a foundation for assisting veterans in the job search process.